Associations of Contact History, Smoking Status, Nutrition Status, Anti Retrovirus Treatment, and TB HIV Co-infection Among People with HIV/AIDS - Adymulianto Manurung (Journal of Epidemiology and Public Health, 2019)
Background: Tuberculosis (TB) and HIV co-infection causes a heavy burden on health care systems and poses particular diagnostic and therapeutic challenges. Studies into predictors of TB-HIV co-infection is lacking in Indonesia. This study aimed to examine the associations of contact history, smoking status, nutrition status, ARV treatment, and TB HIV co-infection among people with HIV/AIDS (PLWH).Subjects and Method: This was a unmatched case-control study conducted in Balige, North Sumatera. A sample of 82 people living with HIV/AIDS was selected for this study, comprising 41 cases with and 41 controls without TB-HIV co-infection. The dependent variable was TB-HIV co-infection. The independent variables were contact history, smoking status, nutrition status, and anti retroviral (ARV) treatment. The data on HIV/AIDS co-infection were taken from the medical record at HKBP Committee HIV/AIDS service. Other variables were measured by questionnaire. Data were analyzed by a multiple logistic regression.Results: 82.9% of PLWH had no contact history with TB patients, 56.1% had poor nutrition status, 78% were smokers, and 58.5% had irregular ARV treatment. The risk of TB HIV co-infection increased with poor nutrition status (OR=3.48; p=0.014), smoking (OR=3.39; p=0.021), and irregular ARV treatment (OR=10.16; p<0.001). Test results multiple ARV treatment is the most dominant variable affecting the incidence of TB-HIV co-infection (OR= 8.04; 95% CI= 2.47 to 26.18; p<0.001).Conclusion: The risk of TB HIV co-infection increases with poor nutrition status, smoking status, and irregular ARV treatment.Keywords: TB, HIV co-infection, nutrition status, smoking, ARV treatment, people living with HIV/AIDSCorrespondence: